Orbital Angular Momentum Optical Amplifier Based on PbS-Doped Ring-Core Fiber - Xu, Lingmin; Shang, Yana; Yang, Jinhong; Chen, Zhenyi; Pang, Fufei; Liu, Huanhuan; Dong, Yanhua; Chen, Na; Wen, Jianxiang; Wang, Tingyun (Frontiers in Physics, 2020)
A unique orbital angular momentum (OAM) optical amplifier based on a ring-core fiber doped with lead sulfide (PbS) is realized for the first time in this study. The PbS-doped ring-core fiber is fabricated using the modified chemical vapor deposition method. The cross-sectional microscope image of the fiber is obtained. The difference in the refractive index between the ring core and the fiber cladding measured by a three-dimensional refractive index tester reaches 1%. The sulfur and lead content in the ring-core of the PbS-doped ring-core fiber is confirmed by energy spectrum analysis. A first-order OAM optical amplifier is built based on the PbS-doped ring-core fiber. The experiment confirms that the air-hole PbS-doped ring-core fiber can support the OAM |l| = 1 modes. In addition, 2.3 dB of on–off gain is obtained for the OAM |l| = 1 modes at 1,550 nm. The fluorescence spectrum obtained using the backward pumping method ranges from 1,100 to 1,600 nm.